Age variation in a fluctuating population of the common vole - Jánová, Eva; Heroldová, Marta; Nesvadbová, Jirina; Bryja, Josef; Tkadlec, Emil (Oecologia, 2003)
We analysed variation in age in a fluctuating population of the common vole ( Microtus arvalis) in southern Moravia, Czech Republic, to test the assumption of the senescence hypothesis that the age of voles increases with increasing population density. Between 1996 and 1998, we monitored the demographic changes by snap-trapping and live-trapping in a field population passing through the increase, peak and decline phase of the population cycle. We used the eye lens mass method to determine the age of snap-trapped animals and those that died in live-traps. The average age of winter males was clearly higher after the peak phase breeding season than before it. No such phase-dependent shift in age, however, was observed in the female component. Male age continued to increase from autumn to spring over the pre-peak winter, and the highest age was in spring of the peak phase year. However, after the peak phase breeding season the highest age was achieved in winter, with the decline phase males during the next spring tending to be younger. The average age of females in spring populations was always lower than in winter populations. The average age of voles from live-traps was always higher than voles from snap-traps, particularly in winter and spring populations, suggesting the presence of senescent animals. Although the density-dependent changes in age are consistent with those observed for other voles, they provide only weak evidence that population cycles in the common vole are accompanied by pronounced shifts in individual age, particularly in female voles.
Keywords: sexuální faktory; věkové faktory; Seasons; Age Factors; mužské pohlaví; rozmnožování; ženské pohlaví; Reproduction; zvířata; Population Dynamics; Female; populační dynamika; roční období; Sex Factors; Arvicolinae; Male; Animals